Carbonic anhydrase in minor salivary glands of quail: histochemistry versus immunohistochemistry. (February 2014) - Gabrielli, Maria Gabriella; Tomassoni, Daniele
Abstract Studies on the mechanisms of saliva secretion have indicated that carbonic anhydrase (CA) is expressed in mammalian salivary glands. The enzyme is present in the saliva as the only known secretory isoenzyme, CAVI; its activity has been related to the modulation of taste and caries development. Unlike mammals, in birds, saliva is produced by the so-called minor salivary glands, mostly concentrated in the tongue. The involvement of CA has never been explored in avian salivary secretion. Thus, we aimed here to ascertain the enzyme occurrence in the quail lingual glands by a parallel investigation of the distributional patterns of CA activity sites, as visualized by histochemistry, and the immunohistochemical patterns of cytosolic CAII and secretory CAVI. The comparative evaluation of our findings does not rule out that some CA isoforms, associated to basolateral borders of the secretory cells and antigenically different from cytosolic CAII and secretory CAVI, may be involved in the salivary secretion in the quail lingual glands.